2018
DOI: 10.1002/jcp.27500
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of long noncoding RNA urothelial carcinoma associated 1 inhibits colorectal cancer cell proliferation and promotes apoptosis via modulating autophagy

Abstract: Long noncoding RNA urothelial carcinoma associated 1 (UCA1) has been implicated in the growth and metastasis of colorectal cancer (CRC), and autophagy contributes to tumorigenesis and cancer cell survival. However, the regulatory role of UCA1 in CRC cell viability by modulating autophagy remains unclear. In the present study, a significant positive correlation was observed between UCA1 and microtubuleassociated protein 1 light chain 3 (LC3) levels, and the elevated UCA1 was negatively correlated with the PKB/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…LncRNAs were recently demonstrated to play vital roles as major regulators of gene expression and cancer cell proliferation (24) in multiple cancers. Several lncRNAs have been identified as regulators in CRC cell proliferation and metastasis (25). In current study, we focused on a cancer-related lncRNA, LINC00114, which we found to be upregulated in CRC.…”
Section: Discussionmentioning
confidence: 98%
“…LncRNAs were recently demonstrated to play vital roles as major regulators of gene expression and cancer cell proliferation (24) in multiple cancers. Several lncRNAs have been identified as regulators in CRC cell proliferation and metastasis (25). In current study, we focused on a cancer-related lncRNA, LINC00114, which we found to be upregulated in CRC.…”
Section: Discussionmentioning
confidence: 98%
“…Instead, autophagy activator RAPA reversed the effect. Therefore, down-regulation of UCA1 induces autophagy inhibition by activating the AKT/mTOR signaling pathway, thereby inhibiting cell proliferation and promoting apoptosis of caco2 cells [ 101 ]. Mounting evidence suggests that LncRNA is a key factor in autophagy [ 102 ].…”
Section: The Main Regulatory Factors Of the Interaction Between Autopmentioning
confidence: 99%
“…However, in certain settings, UCA1 positively regulates autophagy. For instance, Song et al reported that knockdown of UCA1 inhibited colorectal cancer cell proliferation and promoted apoptosis via suppression of autophagy. Wu et al demonstrated that UCA1 contributed to the progression and drug resistance of bladder cancer cells through ATG7‐mediated induction of autophagy.…”
Section: Discussionmentioning
confidence: 99%